Policy analysis of the provision and utilisation of sports facilities within the Cape Town municipal area - Clark, S. G.(Sidney Gardiner) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. P. A.) -- University of Stellenbosch, 1987.